Molecular Mechanism of Astragaloside IV in Improving Endothelial Dysfunction of Cardiovascular Diseases Mediated by Oxidative Stress. (19th November 2021) - Meng, Peipei; Yang, Rui; Jiang, Fenjun; Guo, Jianbo; Lu, Xinyu; Yang, Tao; He, Qingyong
Abstract : Endothelial dysfunction, induced by oxidative stress, is an essential factor affecting cardiovascular disease. Uncoupling of endothelial nitric oxide synthase (eNOS) leads to a decrease in nitric oxide (NO) production, an increase in reactive oxygen species (ROS) production, NO consumption, and NO synthesis. As a main active ingredient of astragalus, astragaloside IV can reduce the apoptosis of endothelial cells during oxidative stress. This review is aimed at exploring the mechanism of astragaloside IV in improving oxidative stress-mediated endothelial dysfunction relevant to cardiovascular diseases. The findings showed that the astragaloside IV can prevent or reverse the uncoupling of eNOS, increase eNOS and NO, and enhance several activating enzymes to activate the antioxidant system. In-depth validation and quantitative experiments still need to be implemented.